2013
DOI: 10.1590/s0103-05822013000400020
|View full text |Cite
|
Sign up to set email alerts
|

Auditory steady state response in hearing assessment in infants with cytomegalovirus

Abstract: OBJECTIVE: To report an infant with congenital cytomegalovirus and progressive sensorineural hearing loss, who was assessed by three methods of hearing evaluation. CASE DESCRIPTION: In the first audiometry, at four months of age, the infant showed abnormal response in Otoacoustic Emissions and normal Auditory Brainstem Response (ABR), with electrophysiological threshold in 30dBnHL, in both ears. With six months of age, he showed bilateral absence of the ABR at 100dBnHL. The behavioral observational audiometry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…The auditory steady-state response (ASSR) elicited by periodical auditory stimulation is a major approach in clinic for hearing screening and frequency-specific hearing assessment (e.g., Silva et al, 2013 ; Francois et al, 2016 ). Recently, increasing number of studies have found abnormalities of ASSR in psychiatric disorders such as schizophrenia (O'Donnell et al, 2013 ; Thune et al, 2016 ), autism (Gandal et al, 2010 ), and bipolar disorder (Rass et al, 2010 ; Oda et al, 2012 ; Isomura et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…The auditory steady-state response (ASSR) elicited by periodical auditory stimulation is a major approach in clinic for hearing screening and frequency-specific hearing assessment (e.g., Silva et al, 2013 ; Francois et al, 2016 ). Recently, increasing number of studies have found abnormalities of ASSR in psychiatric disorders such as schizophrenia (O'Donnell et al, 2013 ; Thune et al, 2016 ), autism (Gandal et al, 2010 ), and bipolar disorder (Rass et al, 2010 ; Oda et al, 2012 ; Isomura et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that 10% of children with cCMV present with obvious clinical symptoms at birth and 90% are born without specific clinical signs or symptoms. Approximately 30%–60% of children with symptomatic infection and 10%–15% of children with asymptomatic infection develop SNHL, so the early detection of such infections in children is particularly important ( 101 ). The diagnostic rate of bilateral profound SNHL using a combined genetic deafness test and CMV DNA detection test was reported to be 46.4% ( 102 ).…”
Section: The Future Stage Of Newborn Hearing Screeningmentioning
confidence: 99%